2019
DOI: 10.1101/832089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Incipient local adaptation in a fungus: evolution of heavy metal tolerance through allelic and copy-number variation

Abstract: Human-altered environments can shape the evolution of organisms. Fungi are no exception, though little is known about how they withstand anthropogenic pollution. Here, we document incipient polygenic local adaptation in the mycorrhizal fungus Suillus luteus driven by recent soil heavy metal contamination. Genome scans across individuals from recently polluted and nearby unpolluted soils in Belgium revealed no evidence of population structure but detected allelic divergence and gene copy number variation in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…The role of CNVs in local adaptation has been recognized and understood in plants, animals and fungi (e.g. González and Petrov, 2009; Bazzicalupo et al., 2019; Nelson et al., 2018; Prunier et al., 2019; Zhang et al, 2020). In marine fishes, CNVs have been associated with freeze resistance (Chen et al., 2008; Desjardins, Graham, Davies, & Fletcher, 2012; Hayes, Davies, & Fletcher, 1991; Hew et al., 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The role of CNVs in local adaptation has been recognized and understood in plants, animals and fungi (e.g. González and Petrov, 2009; Bazzicalupo et al., 2019; Nelson et al., 2018; Prunier et al., 2019; Zhang et al, 2020). In marine fishes, CNVs have been associated with freeze resistance (Chen et al., 2008; Desjardins, Graham, Davies, & Fletcher, 2012; Hayes, Davies, & Fletcher, 1991; Hew et al., 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in expression levels of genes that have protective functions against toxins, or that are co-opted by toxins can lead to variation in resistance levels. For instance in humans, natural variation in expression levels of the gene CMG2 is associated with variation in resistance to anthrax ( Martchenko et al 2012 ), and in the fungus Suillus luteus , selection pressure from heavy metal pollution quickly led to copy number variation in transport genes with protective functions against heavy metal toxicity ( Bazzicalupo et al 2019 ). Sensitivity to copper in adult D. melanogaster DSPR strains does not appear to be due to insufficient expression of genes involved with copper or metal detoxification such as MTs or CTR family transporters (Supplementary Table S5).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown distinct roles of CNVs in local adaptation in terrestrial plants and animals (e.g. Tigano et al, 2018;Weetman et al, 2018;Bazzicalupo et al, 2019;Nelson et al, 2018;Prunier et al, 2019;Ruytinx et al, 2019) but empirical studies on CNVs in marine systems remain limited. Previous studies in marine fishes supported a role for CNVs in freeze resistance (Hew et al, 1988;Hayes et al, 1991, Chen et al, 2008Desjardins et al, 2012).…”
Section: Cnv-environment Associations Are Stronger Than Snp-environmementioning
confidence: 99%